Multi-enzymatic complex on growth performance, blood parameters, and economic viability in piglets - Lilian Kelly Pereira Netrebka; Patricia Rossi; Paulo Segatto Cella; Carlos Alexandre Oelke; Jackeline Dall Agnol de Lima; Pedro Valério Dutra de Moraes; Maria Antonia Michels da Souza (Acta Scientiarum. Animal Sciences, 2023)
The aim of the present study was to evaluate the dietary effect of an enzymatic complex on the growth performance variables, blood parameters, and economic viability of piglets. To achieve this, we used 80 piglets (40 castrated males and 40 females) in a 2 × 2 factorial design following a randomized block experimental distribution, with two levels of metabolizable energy (adequate: 3206.09 and low: 3005.45 kcal kg-1) and two enzyme levels (0 and 50 g ton-1). The results showed no significant difference between treatments in the growth performance variables or blood parameters of piglets. The economic viability, economic efficiency index, and cost index were improved when we used a diet with a low energy supplemented with the enzyme complex as compared to other experimental diets. Thus, we concluded that enzyme complex supplementation can maintain growth performance and blood parameters in piglets even when they are fed low energy diets. Moreover, this could reduce production costs.